Critical Reflections on Individual Collages as a Research Method With Young Women Living With HIV in Zambia. Issue 5 (October 2022) - Mackworth-Young, Constance R. S.; Wringe, Alison; Clay, Sue; Chonta, Mutale; Chiiya, Chipo; Konayuma, Katongo; Sievwright, Kirsty; Mbewe, Madalitso; Mwale, Mwangala; Stangl, Anne L.; Bond, Virginia
Art-based research methods can enable young people to generate data that provide insights into their lives. We assessed the feasibility, value, and limitations of collages as a participatory research method to understand the experiences of young women living with HIV. Individual collages were created in participatory workshops, firstly in 2015 and secondly in 2017, by a cohort of young women living with HIV in Lusaka, Zambia. Collages were analyzed visually and thematically and compared to other qualitative methods. Participants engaged readily with making collages and expressed how the collages represented themselves. The collages conveyed aspirations, resilience, optimism, and identities beyond HIV. Other data generation methods focused more on challenges associated with HIV. The second collages demonstrated more complex portrayals of participants' life and developmental transitions. Collages provided a feasible, effective, and therapeutic method of empowering young women living with HIV to tell their own stories and express their full selves.